Socialization Of Understanding The Three Great Sins Of Education To Create A Comfortable And Safe Learning Environment - Rahayu, Sri; Safiri, Ananda Dwi; Ana, Putri; Adisti, Cici; Syafitri, Della; Firanda, Kirna (LPPM STIKOM Tunas Bangsa, 2024)
AbstractThis theory discusses the Three Big Sins of Education, students in Indonesia do not yet understand the three big sins of education in the world of education. The aim of this socialization is to provide students with an understanding of the three big sins of education in order to create a safe and comfortable learning environment and instill the character values of students at MTs Nurul Iman Simpang Empat. This activity method uses a lecture (presentation) method to provide knowledge about the three major educational sins to MTs Nurul Iman Simpang Empat students. From the results obtained, students can learn lessons about actions that should not be carried out such as bullying, sexual violence and intolerance and know how to prevent and avoid them. Apart from that, this socialization must be carried out by the school to provide space to provide students with the need to know the etiquette of friendship, the etiquette of learning, as well as knowing the sanctions received from the impacts caused by bullying and sexual violence. This socialization involved 100 students starting from grades 7-9. This socialization activity was carried out face to face on Wednesday, October 2 2024.rticle. Abstract are created in one paragraph and a maximum of 250 words with font Gill Sans MT 9 pt and single space. In the abstract should contain the background, objectives, methodology, results, and conclusions. Abstract should not contain tables/images without including a citation. The use of abbreviations should be minimum except for units. Abstract does not have to be a translation from indonesian abstract word by word, but has the same content. Objectives and methodology are arranged in the form of past tense, while the results and conclusions in the form of simple present tense.